2012
DOI: 10.1097/bpo.0b013e3182471ac2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Acute Patellar Dislocation in Children

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
128
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(143 citation statements)
references
References 33 publications
5
128
0
10
Order By: Relevance
“…48 With graft strength exceeding the native MPFL, the importance of anatomic MPFL reconstruction and minimizing the effect of the patellar stabilization on areas of articular cartilage damage is compounded in patients with underlying patellar chondropathy-a common finding in patients with patellofemoral instability and history of dislocation. 33 This is particularly significant given the potential for medial facet overload, with a reported 50% increase in peak medial patellofemoral pressure when an overtightened MPFL graft is positioned proximally on the femur. 13 Similarly, Bollier et al 7 reported the complications of medial patellofemoral articular overload, iatrogenic medial subluxation, and recurrent lateral instability in a group of patients with prior anterior and proximal MPFL femoral tunnel malposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 With graft strength exceeding the native MPFL, the importance of anatomic MPFL reconstruction and minimizing the effect of the patellar stabilization on areas of articular cartilage damage is compounded in patients with underlying patellar chondropathy-a common finding in patients with patellofemoral instability and history of dislocation. 33 This is particularly significant given the potential for medial facet overload, with a reported 50% increase in peak medial patellofemoral pressure when an overtightened MPFL graft is positioned proximally on the femur. 13 Similarly, Bollier et al 7 reported the complications of medial patellofemoral articular overload, iatrogenic medial subluxation, and recurrent lateral instability in a group of patients with prior anterior and proximal MPFL femoral tunnel malposition.…”
Section: Discussionmentioning
confidence: 99%
“…6,12,28 Traumatic, acute lateral patellar dislocation is synonymously associated with rupture and/or attenuation of the MPFL in adults 18,37 and in pediatric patients. 33,51 Recurrent instability (including redislocation and painful subluxation) and complete dislocation are reported in up to one-third and one-half of patients, respectively, treated nonoperatively after traumatic, acute lateral patellar dislocation. 38 Likewise, MPFL rupture is considered the essential lesion of chronic lateral patellar instability.…”
mentioning
confidence: 99%
“…Therefore, the purpose of the MRI is to evaluate for the presence of concomitant injuries that could cause continued instability or pain. Seeley M et al [7] noted that adolescents with MPFL pathology have multiple sites of MPFL pathology and that more than 33% have intra-articular pathology. In all cases showing chondral lesions on MRI, surgical intervention was performed, consisting of arthroscopy to address intra-articular pathology, followed by an open MPFL repair.…”
Section: Imaging Evaluationmentioning
confidence: 99%
“…5) [19, 54 -57]. Hier sind die osteochondralen Verletzungen weniger häufig als an der medialen Patella und werden in der Literatur mit bis 40 % angegeben [71,72]. Typische Lokalisation ist die zentrale und laterale Hauptbelastungszone [71,73] …”
unclassified